Pemanfaatan Rumah Kompos sebagai Sarana Upgrading Keterampilan Pembuatan Pupuk Kompos - Siahaan, Ian Hardianto; Jonoadji, Ninuk; Lourentius, Suratno (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Uncontrolled population growth and urban displacement will continue to be the causes of the rise in garbage. Waste that accumulates for too long and becomes dense and scattered will cause pollution, i.e., the spread of pests and unwanted odors. The Abdimas team sees the role of compost houses as an optimal solution to provide knowledge or education while growing public interest and awareness of the importance of garbage control and reusing it to increase the economic value of partners and communities. The purpose of this activity is for the community to be able to have a positive impact on the establishment of other composite houses around it. The activities were conducted in the form of training and supporting workshops at the PCU Composite House, and follow-up of the implementation results was conducted through the visit of the Abdimas team at the location of the partner as a post-execution evaluation of the activities. Implementation of this activity is divided into three stages, namely: preparation of training, implementation of the training, and non-continued application of training results at the partner site. The training event is packed with the topic